Сorporate social responsibility of construction enterprises: status, development trends and implementation policy - Seredyuk, K.V. (Ways to Improve Construction Efficiency, 2023)
Striving for sustainable development in the conditions of globalization processes and in the period of transformation of the country’s economy, assessing the current state of corporate social responsibility (SCR) of construction enterprises, the need to study the state and trends of policy development and its implementation practice is determined. The social responsibility of companies, regarding the sustainable development of the whole society, is an important approach for construction enterprises in responding to new social and environmental problems. An important aspect of modern civilized business, including construction, is the basis of the csr concept, the implementation of which in the field of enterprise management has an extremely important direction not only for creating a positive image of the company, but also for increasing its competitiveness both on a global scale and at regional levels management. Therefore, the expediency of combining csr activities with the specifics of the company, which must invest in potentially useful areas of knowledge and innovative solutions, becomes especially important. The efficiency of construction enterprises that implement csr in their activities has not yet reached the optimal level, the influence of institutional factors on csr efficiency is complex and non-linear, and the improvement of csr efficiency in the construction industry depends on both the optimization of the institutional environment and the improvement of the potential of csr efficiency management. The necessary changes in the existing practice of csr management should have a certain systematicity, which should include the integration of csr principles, methods and tools in the economic activity of enterprises in order to ensure their competitiveness, achieve high productivity and profitability. The research was carried out with the help of a review of scientific literature, modern studies of expert organizations, public organizations and policy research on csr issues of construction enterprises. The results of the study showed that there have been major positive changes in the evolution of the csr concept in ukraine over the past few years, but there are still some unresolved problems with which enterprises are forced to work.